Bunga Kamboja pada Feminine Romantic Style - Resfi Novita Putri; Nofi Rahmanita; Desra Imelda; Mirda Aryadi (PT. AHLAL PUBLISHER NUSANTARA, 2026)
The work titled Plumeria in Feminine Romantic Style draws inspiration from the Plumeria flower (Plumeria alba), translating its essence into garments that embody a feminine, romantic aesthetic. This project serves as a platform to showcase and promote the Plumeria inspired designs to the public. The collection comprises a blouse, a skirt, a long dress, and a skirt with a trailing train. Plumeria motifs are incorporated into Tando Pusako batik a traditional textile from Mukomuko, Bengkulu to complement the garments. The color palette is derived directly from the Plumeria flower, featuring soft pastels such as muted yellow, white, soft green, and muted brown. For this final project, the creator presents three categories of fashion ready to wear, ready to wear deluxe, and haute couture. These are crafted using a blend of high-quality materials, specifically Yamaha silk satin and Tando Pusako batik. Corsage and beadwork techniques are employed to highlight garment details the corsage technique creates three dimensional accents that lend a luxurious feel to the outfits. The design process involved field exploration, a study of cultural heritage, and design development that aligns with current fashion trends while preserving traditional identity. This project serves not only as an artistic endeavor but also as a medium for cultural preservation, fostering appreciation for traditional textiles, and introducing cultural heritage into the modern fashion landscape. The collection was unveiled at a fashion show held at the Hoeridjah Adam Building at ISI Padangpanjang. It is hoped that this work will instill a sense of pride in the younger generation regarding the development of fashion rooted in local culture. The resulting pieces include the ready to wear outfit Rona Kamboja (Plumeria Hue), the ready to wear deluxe outfit Pesona Kamboja (Plumeria Charm), and the haute couture outfit Blooming Serenity. Keywords: Frangipani Flower, Feminine Romantic Style, Batik Tando Pusako Abstrak Karya yang berjudul